Photochemical reactions in the atmosphere – a source of secondary pollutants - Cuciureanu, R.; Dimitriu, G. (Інститут програмних систем НАН України, 2006)
In the atmosphere polluting agents are involved in different reactions which lead to secondary pollutants. Secondary pollutants are mainly generated by photochemical and thermal reactions. These reactions occur in the atmosphere and they generate photochemical smog. We studied the variations of primary and secondary pollutants concentrations by photochemical modeling systems. All the test problems (denoted models A-F) were coded in Fortran and are based on the Carbon Bond Mechanism IV consisting of 32 chemical species involved in 70 thermal and 11 photolytic reactions. The numerical integration of the stiff systems was carried out using a Rosenbrock solver.